Application Receipt Claims on PT. Blue Bird Group using Microsoft Visual Basic 6.0 - Muhammad Iqbal Basith; Soenarto Usna, SSi, MMSI (Jurnal Sistem Informasi, 2005)
Invoice receipt is a letter received by the suppliers of the company PT. Blue Bird, which is temporary and used to collect payment on PT. Blue Bird. This process is usually done by employees with the manual way, so the possibility of human error in the data storage process is very large. This was due to the lack of applications and places to accommodate a portion of the claim data into one place. For that writers create applications that can assist companies in managing performance data and storing bills into a database, so that data security can be maintained adequately.